Generation of IDF Equation from Catchment Delineation Using GIS - Mahmud Al Islam; Hasibul Hasan (Salehan Institute of Higher Education, 2020)
The study was intended to find out the catchment characteristics of an area and the IDF (Intensity-Duration-Frequency) analysis of rainfall of that area using Gumbel method and Log Pearson type III method. In different studies, the IDF equations are generated for an area without acknowledging the catchment, stream length of the catchment and the time of concentration. In our study the Digital Elevation Map (DEM) of Dhaka was used. The DEM was analyzed using QGIS to find out different catchments, catchment area, catchment slope, stream length etc. The rainfall data of 18 years was collected from BMD (Bangladesh Meteorological Department) at 24 hours’ interval. This rainfall data was analyzed using Gumbel method and Log Pearson Type III method because these methods give accurate prediction for return period more than the range of the acquired data. The return period was taken as 2 years,5 years,10 years,25 years,50 years and 100 years. Finally, the intensity for different return period was plotted against the duration of the rainfall to find out the IDF curve. For any kind of rainfall analysis to find the peak discharge for designing storm sewage lines, small hydraulic structures or calculating surface runoff, infiltration, sub-surface runoff, discharge at rivers or water bodies, the derived IDF equations can be used. Even to find out peak discharge with a return period more than 18 years these set of equation can be used. This method can also be used in other sub urban or urban areas to find out the time of concentration of that catchment and IDF relationships for short duration rainfalls.